Research of load characteristics of wireless power transmission system based on magnetic coupling resonance - XUE Hui; LIU Xiaowen; SUN Zhifeng; ZHANG Guoyuan (Gong-kuang zidonghua, 2015)
In order to study the influence of load on transmission performance of wireless power transmission system, circuit model of wireless power transmission system based on magnetic coupling resonance was established. The analytical expression of the minimum load to avoid frequency splitting and the optimal matching load calculation model with the maximum received power were obtained by using circuit coupling theory. At the same time, the minimum load is always less than the optimal matching load. The simulation results show that increasing the load value can inhibit the frequency splitting phenomenon for different coupling coefficient; When receive power is the maximum, the best matching load values is changed with the difference of coupling coefficient, and there always will be the best matching load. The conclusion can provide theoretical guidance for load selection of the wireless power transmission system.